2015
DOI: 10.1039/c4cc07231f
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel interactors of human telomeric G-quadruplex DNA

Abstract: A chemoproteomic-driven approach was used to investigate the interaction network between human telomeric G-quadruplex DNA and nuclear proteins. We identified novel G-quadruplex binding partners, able to recognize these DNA structures at chromosome ends, suggesting a possible, and so far unknown, role of these proteins in telomere functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 37 publications
(21 reference statements)
1
32
0
1
Order By: Relevance
“…Indeed, many natural proteins have been identified that interact with G4s (see G4 Interacting Proteins Database, http://bsbe.iiti.ac.in/bsbe/ipdb/) [61]. The identification of G4 associated proteins has mostly relied on affinity proteomics experiments employing RNA and DNA G4 oligomers as baits to isolate G4 interactors from cellular extracts [62][63][64][65]. Other approaches involve computational analysis of genomic protein binding sites to assess the enrichment of predicted G4 motifs within these binding sites [54,66], or meta-analysis, in which shared structural features of G4-binding protein domains were compared to predict new putative G4 interactors [67,68].…”
Section: Natural G4-binding Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many natural proteins have been identified that interact with G4s (see G4 Interacting Proteins Database, http://bsbe.iiti.ac.in/bsbe/ipdb/) [61]. The identification of G4 associated proteins has mostly relied on affinity proteomics experiments employing RNA and DNA G4 oligomers as baits to isolate G4 interactors from cellular extracts [62][63][64][65]. Other approaches involve computational analysis of genomic protein binding sites to assess the enrichment of predicted G4 motifs within these binding sites [54,66], or meta-analysis, in which shared structural features of G4-binding protein domains were compared to predict new putative G4 interactors [67,68].…”
Section: Natural G4-binding Proteinsmentioning
confidence: 99%
“…In accordance with the G4 forming potential of the telomere repeat sequence, many telomere-associated proteins have been shown to interact with G4 structures [63]. For instance, POT1 [75] and RPA [76], two components of the shelterin complex, as well as the human CST complex [77], are able to bind and unwind telomeric G4 structures and assist the action of telomerase.…”
Section: Natural G4-binding Proteinsmentioning
confidence: 99%
“…HMGB1 binding with the linker region of nucleosomal DNA destabilizes the nucleosome structure (presumably due to DNA bending) and thus promotes nucleosome sliding and remodeling . HMGB1 has been identified as a binding partner of telomeric G4 in a pull‐down assay and the initial in vitro comparative studies with promoter G4s confirmed HMGB1 selectivity for the telomeric quadruplex structure . However, subsequent studies revealed that HMGB1 also has a high affinity for the KRAS promoter G4 .…”
Section: G4s Might Directly Engage Architectural Chromatin Proteins mentioning
confidence: 99%
“…In conclusion, we have described the synthesis of an ew chiral ligand (R/S)-L with ap yridine donor and ag lycol backbone,w hich can be incorporated internally into oligonucleotide strands.I naunimolecular human telomeric G-quadruplex, one G-tetrad can be replaced by four such ligands that are preorganized to coordinate to ac opper ion, thus stabilizing the structure.U sing the metal-base tetrad within a Tetrahymena telomeric G-quadruplex enables the switching of topologies from ah ybrid-dominated conformer mixture to an antiparallel strand arrangement, as confirmed by UV melting curves and CD analysis.T he incorporation of four pyridine ligands into the 15mer thrombin-binding aptamer permits copper-triggered control over thrombincatalyzed fibrinogen hydrolysis,asdemonstrated by aclotting assay.S witchable G-quadruplex folding may be of value in protein affinity assays, [10,31] where paramagnetic metal ions will enable EPR-based readout. In addition, we are currently extending this concept to systems containing other metals and ligands.T he herein introduced incorporation of several ligands into as ingle-stranded G-quadruplex allows for heteroleptic ligand combinations aimed at biohybrid coordination environments with tunable catalytic functions and redox properties.…”
Section: Communicationsmentioning
confidence: 99%